Growing Teaching Motivation for Future Teachers Through Microteaching - Soraya, Dila Umnia; Patmanthara, Syaad; Kusuma Ningrum, Gres Dyah (Universitas Negeri Malang, 2022)
The teacher is the main foundation for implementing successful learning in delivering students to achieve their goals and aspirations. Teacher in learning does not only transfer knowledge but also transfers positive values that will equip students to live in society. The meaning of learning for teachers and students cannot be separated from the teacher's role as a motivator. Apart from having to have basic teaching skills, teachers are also required to have self-motivation in teaching. One of the efforts to train and improve basic teaching abilities and skills for student teacher candidates is through microteaching. This step is also an effort to increase the teaching motivation future teachers at educational universities, especially the State University of Malang. The purpose of this study is to determine the level of teaching motivation future teachers who have implemented microteaching, in terms of 2 indicators, namely intrinsic and extrinsic motivation. This research is a quantitative descriptive with 142 students from 8 faculties of education at Malang State University as subjects. The research instrument uses a closed questionnaire with a Likert scale that has been tested for validity, reliability, and normality. Data were analyzed descriptively to measure the level of teaching motivation future teachers at Malang State University. The results of the study show that the teaching motivation for future teacher students is mostly at a moderate level. While the percentage of intrinsic motivation is higher than the extrinsic motivation. So it can be concluded that microteaching activities have succeeded in growing future teachers' teaching motivation, especially on intrinsic motivation. The desire to succeed, the encouragement and need in teaching, as well as the hopes and aspirations for the future are the driving force behind teaching motivation for future teacher students at the State University of Malang.